Phase II Study of Paclitaxel in Patients With Soft Tissue Sarcomas. (1997) - Patel, Shreyaskumar R.; Linke, Kaye A.; Burgess, M. Andrew; Papadopoulos, Nicholas E.; Plager, Carl; Jenkins, Jan; Benjamin, Robert
Abstract : Purpose . Patients with soft tissue sarcoma (STS) who have previously received standard chemotherapy including adriamycin (doxorubicin), ifosfamide, cyclophosphamide and DTIC (dacarbazine) have very limited therapeutic options. It is important to identify new drugs with some activity in this disease and we therefore undertook this trial to determine the antitumor activity of paclitaxel (Taxol). Methods . We conducted a phase II study of paclitaxel in patients with STS who had received prior standard chemotherapy. Paclitaxel was administered at a starting dose of 200 mg m − 2 as a 24-h infusion with STS premedication, every 21 days or upon hematologic recovery (absolute granulocyte count (AGC) ≥ 1500/ μ l, platelets ≥ 100 000/ μ l). Neupogen was not used routinely. The study was conducted based on a two-stage design proposed by Simon. Responses were assessed radiographically using standard criteria. Results . Nineteen eligible patients were treated in the first stage of the study. The median age was 50 years (range 20–68 years), and there were nine females and 10 males with Zubrod performance status of 1 or 2. One patient achieved a minor response. Median AGC nadir was 0.1/ μ l on day 12 with absolute neutropenia lasting 5 days. Median platelet nadir was 171 000/ μ l on day 9. There were no grade 3/4 non-hematologic toxicities and no deaths related to treatment. Discussion . Paclitaxel, at this dose and schedule, is well tolerated but inactive in this patient population.